The effects of a complex yoga-based intervention on healthy psychological functioning - Koncz, Adam; Nagy, Eszter; Csala, Barbara; Körmendi, János; Gál, Vera; Suhaj, Csilla; Selmeci, Csongor; Bogdán, Ágota Selmeciné; Boros, Szilvia; Köteles, Ferenc (Frontiers in Psychology, 2023)
Background Yoga based interventions were found to have a positive impact on various indicators of psychological functioning, such as perceived stress, satisfaction with life, positive and negative affectivity. Additionally, such interventions improved bodily or interoceptive awareness and spirituality. Methods The present study assessed the effects of a 3-month long complex yoga-based intervention compared to a passive control group in a Hungarian community sample. The final sample consisted of 44 intervention (Mage = 47.5, SD = = 8.76) and 29 control participants (Mage = 47.4, SD = 9.47). The aforementioned constructs were measured 1 week before and after the intervention. Results The intervention reduced participants’ perceived stress (p = <0.001, ηp2 = 0.153) and negative affectivity (p = 0.019, ηp2 = 0.113), improved spirituality (p = 0.048, ηp2 = 0.054) and various aspects of interoceptive awareness such as noticing (p = <0.001, ηp2 = 0.169) attention regulation (p = <0.001, ηp2 = 0.211), self-regulation (p = 0.002, ηp2 = 0.190) body listening (p = 0.010, ηp2 = 0.097), trusting (p = 0.026, ηp2 = 0.070), but did not impact positive affectivity and satisfaction with life. Conclusion A 3-months long complex yoga-based intervention has a positive impact on many aspects of healthy psychological functioning.